Entre charges e escritas: as experiências educativas de Claudius Ceccon. - Villwock, Aparecida de França (2013)
The purpose of this study is to present the figure of a Brazilian who was side by side with Paulo Freire in exile, discussing social issues and also working towards a conscious education, politics and citizen. This paper research the biography of the cartoonist, architect, writer and journalist Claudius Ceccon, seeking to present their diverse artistic and intellectual production, highlighting this research analysis of their production charges. One of his early educational interventions was their participation in the Institute of Cultural Action (IDAC), at Geneva, Switzerland - a space for discussions of projects focused on popular education in the countries of Latin America, Europe and Africa Continent.IDAC today has its extension in Rio de Janeiro with the Center for Creation and Image Popular (CECIP), which develops projects related to intellectual emancipation and citizenship. From the context of IDAC, explains to about the period of the civil-military dictatorship (1964-1985), and the role of Claudius Ceccon, in Brazil and in the countries in which he lived during his exile. Noteworthy the time frame (1964-1988), interconnected biography of Claudius and civil-military dictatorship, one political and economic process, in which the country found itself susceptible to radical changes. Therefore, the trajectory of Claudius is striking the context of dictatorship, being one of the consequences the exile, his contribution to the creation of the Pasquim, a newspaper circulation and reference that challenged prevailing paradigms of morality and politics, as well as the IDAC and CECIP are references binding to the biography of Claudius. By highlighting Claudius Ceccon as intellectual, we list the importance of genre charge text in its production, because on searching new means of transmitting knowledge, it becomes necessary to consider diverse ways to address certain issues. Regarding the charges of Claudius highlight his criticism of social life, which challenge values and "established truths". Later this considerations we search in this study to check the following point: which is the paper of Claudio Ceccon illustrations in front of the social, political and educational context to each approaching moment, during his acting at IDAC, Pasquin and in his other publishing articles?